Combining a performance estimation methodology with a hardware - Baghdadi, A. (IEEE Transactions on software engineering)
This paper addresses performance estimation and architecture exploration issues within the context of hardware/software codesign. We introduce a new methodology to rapidly explore the large design space encountered in hardware/software systems. The proposed methodology is based on a fast and accurate estimation approach. This estimation approach takes advantage of both system and RT levels of abstraction, and combines both static and dynamic analysis techniques, in order to obtain the best trade-off between speed and accuracy. It has been implemented as an extension to a hardware/software codesign flow to enable the exploration of a large number of multiprocessor architecture solutions from the very start of the design process. The effectiveness of the proposed methodology is illustrated by a significant application example. Experimental results indicate strong advantages of the proposed methodology.